?CHEMICAL CONSTITUENTS OF CAESALPINIA BONDUC - ALl, M. SHAIQ; SHAMEEL, SIMIN; AHMAD, VIQAR UDDIN; GHANI, K. USMAN (Biological Sciences - PJSIR, 1997)
The seeds of Caesalpinia bonduc (L.) Roxb. belonging to the family Caesalpiniaceae were used as a folk medicine to treat asthma and chronic fever. They were found to be very potent as an antiperiodic, antipyretic and utilized as febrifuge, antispasmodic, antirheumatic and mild purgative [1-2]. Lit- erature survey revealed the presence of diterpenoids such as o-caesalpin [3-4], ~-caesalpin [3,4], o-caesalpin [4,5], y- caesalpin [3-6] and e-caesalpin [7] from the seeds of Cae- salpinia bonduc (L.) Roxb. [syn. C.bonducella (L.) Fleming]. Our phytochemical investigations have led to the isolation of four triterpenoids e-amyrin [12~ursen-3~-01] (I), ~-amyrin [12-0Ieanen-3~-01] (2),lup-20(29)-en-3~-01 (3), lup-20(29)- en-3~-yl acetate (4), and two sterols ~-sitosterol [24(R)- stigmast-f-en-Sjl-ol] (5), ~-sitosteryl galactoside [3-0-~-D- galactopyranosy l-stigmasta-5-ene] (6).